Systematic design of amaximum water recovery network for an urban system based on Pinch Analysis - S. R., Wan Alwi; Zainuddin, Abdul Manan; Zain, Ujang (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/